Pengaruh Harga, Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Iphone Di Kota Malang (Studi Kasus Pada Konsumen Iphone FineApple_ID) - Muhammad Syahrul Ansori; Muhammad Mansur; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine and analyze the effect of price, brand image and product quality on iPhone purchasing decisions in the city of Malang. The population in this study are iPhone consumers who have purchased products at Fineapple id. The data collection method in this study used a questionnaire with a sample of 75 respondents. The independent variable in this study is the effect of price, brand image and product quality and the dependent variable is the purchase decision. The analytical method used in this study is multiple linear regression analysis and processed using SPSS 26. The results of this study simultaneously show that the effect of price, brand image and product quality has a positive and significant effect on purchasing decisions. Partially, Brand Image and Product Quality have a significant effect on iPhone Purchase Decisions, while Price has no effect on iPhone Purchase Decisions Keywords: Price, Brand Image, Product Quality and Purchase Decision.